2022
DOI: 10.3390/pharmaceutics15010017
|View full text |Cite
|
Sign up to set email alerts
|

Embedding of Poorly Water-Soluble Drugs in Orodispersible Films—Comparison of Five Formulation Strategies

Abstract: The poor bioavailability of many newly developed active pharmaceutical ingredients (APIs) poses a major challenge in formulation development. To overcome this issue, strategies such as the preparation of amorphous solid dispersions (ASDs), and the application of the APIs in lipid nanocarriers or the wet-milling of the substances into nanoparticles have been introduced. In addition to an efficient formulation strategy, a dosage form that is accepted by all patients is also of great importance. To enable a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…The surface area may be increased by micronisation made by ultrasonication which finally leads to greater dissolution behaviour [ 42 ]. Interesting studies were performed by Steiner et al Five different formulation strategies were closely investigated regarding their impact on API bioavailability: the preparation of amorphous solid dispersions, embedding of the APIs in a lipid nanosuspension and a lipid nanoemulsion, and the embedding of API nanoparticles or micronized API particles in the film-forming matrix [ 43 ].…”
Section: Technological and Formulation Overviewmentioning
confidence: 99%
“…The surface area may be increased by micronisation made by ultrasonication which finally leads to greater dissolution behaviour [ 42 ]. Interesting studies were performed by Steiner et al Five different formulation strategies were closely investigated regarding their impact on API bioavailability: the preparation of amorphous solid dispersions, embedding of the APIs in a lipid nanosuspension and a lipid nanoemulsion, and the embedding of API nanoparticles or micronized API particles in the film-forming matrix [ 43 ].…”
Section: Technological and Formulation Overviewmentioning
confidence: 99%
“…However, different solubility‐enhancing formulation strategy has its pros and cons. The suitable formulation method should be considered according to the lipophilicity of APIs as well 21 . Additionally, thiolation of polymeric excipients enables to improve the solubility of less water‐soluble drugs as well.…”
Section: Odfs As the Potential Carrier For Various Ingredientsmentioning
confidence: 99%
“…The simplification of the formulation process and the enhancements in drug solubility and bioavailability have positioned the ODF as a promising drug delivery method for loratadine. In another interesting investigation, poorly aqueous soluble drugs such as fenofibrate and naproxen were formulated as nanoparticles using various strategies and were incorporated into ODFs [ 146 ]. The research findings revealed that the dose of API that can be administered in a single ODF significantly relies on the chosen formulation approach and the physicochemical characteristics of the API.…”
Section: Nanoparticle-embedded Odfsmentioning
confidence: 99%